Variability of key performance indicators of Falcon AP. Bren on losing and winning matches in the MSC 2024 final against Selangor Red Giant - Masran, Muhammad Aizarul; Habib’Aini, Nur Aiman Alhakim; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Raja Hussain, Raja Nurul Jannat; Shari, Maisarah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study analyzes the performance patterns and tactical elements of the 2024 MSC Final between Falcon AP Bren and Selangor Red Giant to address the research gap in mobile esports performance analysis. As professional titles like Mobile Legends: Bang Bang increasingly mirror traditional sports in strategic complexity, this research utilizes structured notational and statistical analysis to examine gameplay indicators and decision-making processes. By identifying the key variables that influence match outcomes, the findings provide a data-driven framework for strategy development and competitive optimization within the rapidly evolving mobile esports landscape.